Ammonia inhalation does not increase deadlift 1- repetition maximum in college-aged male and female weight lifters - Vigil, J. N.; Sabatini, P. L.; Hill, L. C.; Swain, D. P.; Branch, J. D. (The Journal of Strength and Conditioning Research, 2018)
Ammonia inhalant use by powerlifters and weight lifters is a prevalent practice with little research support for improved performance. The purpose of this study was to investigate the effects of ammonia as a stimulant on athletic performance during a deadlift 1-repetition maximum (1RM) absolute strength test. Subjects (men: n = 10, mean ± SD age = 21 ± 1 year, mass = 72.5 ± 6.8 kg; and women: n = 10, age = 22 ± 5 years, mass = 66.2 ± 8.1 kg) were required to have at least 2 years of resistance training experience while lacking a history of asthma, lightheadedness, fainting, anaphylaxis, sickle cell traits, and other respiratory disorders. After a baseline 1RM test, subjects were paired by 1RM performance and gender, then randomly assigned in a counterbalanced treatment order to control (water) or ammonia trials after a minimum 72-hour recovery period for another 1RM test involving attempts at 100.0, 102.5, 105.0, and 107.5% of the established 1RM value. Testing was then repeated after the minimum rest period for the remaining trial. Results revealed the expected gender main effect for absolute deadlift 1RM (93.0 ± 29.5 [women]; 152.0 ± 29.5 kg [men]; p < 0.001), but no trial main effect (p = 0.874) or gender by trial interaction effect (baseline = 93.0 ± 15.3, 151.8 ± 42.3 kg; water = 92.0 ± 12.5, 150.9 ± 37.8 kg; ammonia = 92.5 ± 16.4, 153.4 ± 37.9 kg) for women and men, respectively (p = 0.559). Within the limitations of this study, there is no support for the practice of ammonia inhalation to improve deadlift 1RM in training or competition.